Coculture of amylolytic strain and saccharomyces cerevisiae for ethanol production - Suriah Murthy, A/L Thanaveloo (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The objective of this study was to test the hypothesis if the coculture of an amylolytic strain isolated from local ragi tapai and Saccharomyces cerevisiae CSI-1 is able to perform ethanol fermentation efficiently. The amylolytic strain isolated from local ragi tapai was cultivated in raw sago starch and after 10 h of fermentation was inoculated with a culture of Saccharomyces cerevisiae. The results showed that the coculture was able to produce only 1.89 g/L of ethanol in 72 h, while the maximum ethanol production at 84 hour was 2.55g/L. In conclusion, the use of an amylolytic strain and Saccharomyces cerevisiae could be a good technique to enhance the ethanol production to reduce the use of enzymes and cost of ethanol production. Further studies are necessaries to enhance the performance of this coculture.